Teacher leadership in professional development schools - Hunzicker, Jana (Emerald Publishing Limited, 2018)
This edited collection occupies a unique position as the first book to explore teacher leadership within the context of professional development schools (PDSs) and other school-university partnerships in the United States. In today's educational climate of data, differentiation, and accountability, teacher leadership is essential. Professional development schools and other school-university partnerships support teacher leader development by prioritizing teacher learning, modeling best practices, encouraging instructional innovations, and pursuing educational research and other scholarly work. Because PDSs and other school-university partnerships offer distinctive occasions for teachers to engage in leadership roles and responsibilities, a closer look at teacher leadership within these contexts provides a valuable opportunity for the instruction and inspiration of all educators. Written for aspiring teacher leaders as well as for those who teach, research, serve, supervise, and lead in PDSs and other school-university partnerships, 'Teacher Leadership in Professional Development Schools' will immerse readers in deep exploration of teacher leadership across three broad areas: Teacher Leadership and Student Learning; Definitions, Structures, and Cultures that Promote Teacher Leadership; and Teacher Leader Preparation and Development. Following a thought-provoking foreword and two introductory chapters, each of the book's three sections features three to four research-based chapters, written by higher education faculty and practicing P-12 teachers and administrators; a scholarly synthesis chapter, written by a known expert in the field; and three to four teacher leader reflections, written by aspiring, developing, and veteran teacher leaders from across the United States.